The Influence of Price, Product Innovation, and Service Quality on Competitive Advantage (Study on Hartini MSME Customers in Ponorogo) - Melinda Wahyuning Putri; Budi Prabowo (Universitas KH. Abdul Chalim Mojokerto, 2025)
This research seeks to examine how price, product innovation, and service quality affect the competitive advantage of Hartini MSMEs in PonorogoUtilizing a quantitative method with an associative approach, this study gathers data by administering surveys to 100 respondents who are Hartini MSME consumers, using intentional sampling procedures. Data analysis was carried out by multiple linear regression using SPSS assistance, accompanied by classical assumption testing to ensure model feasibility. It was found through the analysis that all three independent variables together have a significant and positive impact on competitive advantage. Partially, each variable also showed a significant effect, with product innovation being the most dominant factor in driving competitiveness. These findings provide strategic insights for MSMEs to continue to innovate and improve product and service quality in the face of increasing competition.